2013
DOI: 10.2478/afe-2013-0088
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of AlSi21CuNi Alloy’s Quality with Use of ATND Method

Abstract: Majority of combustion engines is produced (poured) from Al-Si alloys with low thermal expansion coefficient, so called piston silumins. Hypereutectic alloys normally contain coarse, primary angular Si particles together with eutectic Si phase. The structure and mechanical properties of these alloys are highly dependent upon cooling rate, composition, modification and heat-treatment operations. In the paper one depicts use of the ATND method (thermal-voltage-derivative analysis) and regression analysis to asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Here, Si was separated from its highly supersaturated melt and the eutectic temperature was lowered, because there was no nucleation. [ 16,32 ] In the study by Pezda et al, [ 33 ] it was shown that strontium content of 0.04–0.06 wt% resulted in a maximum elongation at fracture for the similar aluminum casting alloy EN AC‐43 300. Due to the longer holding time of the melt in the furnace during the TRC process, no subsequent modification was necessary, similarly to the use of Na.…”
Section: Resultsmentioning
confidence: 99%
“…Here, Si was separated from its highly supersaturated melt and the eutectic temperature was lowered, because there was no nucleation. [ 16,32 ] In the study by Pezda et al, [ 33 ] it was shown that strontium content of 0.04–0.06 wt% resulted in a maximum elongation at fracture for the similar aluminum casting alloy EN AC‐43 300. Due to the longer holding time of the melt in the furnace during the TRC process, no subsequent modification was necessary, similarly to the use of Na.…”
Section: Resultsmentioning
confidence: 99%
“…The wear resistance of these alloys is achieved by a higher silicon content, which also increases their strength. However, the improvement in strength and wear resistance is at the expense of machinability and castability [3][4]. A progressive material is the alloy AlSi21CuNiMg.…”
Section: Introductionmentioning
confidence: 99%
“…Application of suitable parameters of individual heat treatments determines obtainment of improved mechanical properties of processed materials [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%